Orzecznictwo sygnalizacyjne Trybunału Konstytucyjnego w latach 2014-2020 - Kuczma, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Signaling loopholes and oversights in the law is among the constitutional competences of the Constitutional Tribunal. However, it is evident that the signaling function of the Tribunal has an incidental character compared to its remaining functions. The article analyses the signaling decisions of the Constitutional Tribunal in the 2014–2020 period. The article concerns the issue of the addressee of signaling provisions, votum separatum, the non-binding nature of these decisions, the reaction to the signaling decisions, and certain remarks de lege ferenda. At the end of the paper, current practice is summarised.
Keywords: constitutional law; Constitutional Tribunal; signalisation; gaps and breaches in the law